Performance management in elite football: A teamwork modeling approach - Marques, J.; Chamari, K. (International Journal of Sports Physiology and Performance, 2023)
Winning matches and getting 3 competition points is commonly established as a key performance indicator (KPI) for elite football (soccer) teams to achieve their objectives during the season. While winning is the responsibility of the football players, sport-science and -medicine practitioners` responsibility is to support them by increasing their availability for matches (a key contributing factor to winning the games and ensuring team success). 1,2 Unfortunately, it is not uncommon to observe sport-science (eg, strength and conditioning coach, physiologist) and -medicine (e.g., physician, physiotherapist) practitioners working in silos in a football setting. As such, we are proposing a teamwork modeling approach for practitioners with elite football teams. Our model comprises specific KPIs to enhance players` performance while reducing injury risk (Figure 1). This model has the potential to attract the attention of practitioners and researchers aiming to prevent injuries and improving players` recovery for enhanced football performance.